Contribuição ao estudo do comportamento estrutural de terças pré-fabricadas em concreto protendido sem armadura transversal - Alvarenga Junior, Luiz Carlos de (2021)
Purlins are thin beams made without transverse reinforcement and are used in the roofing of precast warehouses. The object of study of this research, were precast concrete purlins, which had been produced by a company in the region of São Carlos - SP, and intended for the work already completed. However, these elements presented large deformations, causing visual discomfort in the occupants of the building, as a result, a system of semi-rigid connection through metal plates was adopted by the company. Because they are produced without the use of transverse reinforcement, and the Brazilian standards do not make prescriptions regarding the calculation of the shear force of prestressed purlins, this research was based on NBR 9062:2017, which allows parts of the project to be performed based on tests. Therefore, this work aimed to contribute to the study of the structural behavior of roof purlins, based on the existing database, the tests showed that the failure mode occurred near the diagonal tensile mechanism, and the expression that best describes this result is the EN1168. To evaluate the effectiveness of the connection proposed by the manufacturer, we chose to use non-destructive testing in a factory environment. The connection model adopted by the company proved to be satisfactory, and can be characterized as a semi-rigid connection with restriction factor αr = 0.30, but due to the limitations found in the factory, it was not possible to conduct the tests until failure, so it is not possible to say whether the connection maintains this behavior outside the elastic range.